The concierge at Hokkyoku Department Store. 1 - Nishimura, Tsuchika, 1984- (Seven Seas Entertainment, 2024)
Retail work has never been wilder than in this award-winning manga that inspired the anime movie! Working retail is tough enough with regular human customers, but what about when they’re owls, wolves, koalas…and a woolly mammoth? Welcome to the Hokkyoku Department Store, where new employee Akino’s customers are talking animals–including extinct species! Just like any shopper, each has their own complicated request that Akino must strive to satisfy. From a wealthy laughing owl searching for the perfect present to delight his wife to a thespian sea mink attempting to find a gift for a long-awaited reunion with her father, Akino must learn to meet their needs, while also dealing with her challenging coworkers and elusive floor manager.